Systematic Optimization of the iMALDI Workflow for the Robust and Straightforward Quantification of Signaling Proteins in Cancer Cells. Issue 5 (9th August 2020) - Froehlich, Bjoern C.; Popp, Robert; Sobsey, Constance A.; Ibrahim, Sahar; LeBlanc, Andre M.; Mohammed, Yassene; Aguilar‐Mahecha, Adriana; Poetz, Oliver; Chen, Michael X.; Spatz, Alan; Basik, Mark; Batist, Gerald; et al.
Abstract : Purpose: Immuno‐MALDI (iMALDI) combines immuno‐enrichment of biomarkers with MALDI‐MS for fast, precise, and specific quantitation, making it a valuable tool for developing clinical assays. iMALDI assays are optimized for the PI3‐kinase signaling pathway members phosphatase and tensin homolog (PTEN) and PI3‐kinase catalytic subunit alpha (p110α), with regard to sensitivity, robustness, and throughput. A standardized template for developing future iMALDI assays, including automation protocols to streamline assay development and translation, is provided. Experimental Design: Conditions for tryptic digestion and immuno‐enrichment (beads, bead:antibody ratios, incubation times, direct vs. indirect immuno‐enrichment) are rigorously tested. Different strategies for calibration and data readout are compared. Results: Digestion using 1:2 protein:trypsin (wt:wt) for 1 h yielded high and consistent peptide recoveries. Direct immuno‐enrichment (antibody‐bead coupling prior to antigen‐enrichment) yielded 30% higher peptide recovery with a 1 h shorter incubation time than indirect enrichment. Immuno‐enrichment incubation overnight yielded 1.5‐fold higher sensitivities than 1 h incubation. Quantitation of the endogenous target proteins is not affected by the complexity of the calibration matrix, further simplifying the workflow. Conclusions and Clinical Relevance: This optimized and automated workflow will facilitate the clinical translation of high‐throughput sensitive iMALDI assays for quantifying cell‐signaling proteins in individual tumor samples, thereby improving patient stratification for targeted treatment.